2023
DOI: 10.1108/bpmj-04-2022-0179
|View full text |Cite
|
Sign up to set email alerts
|

Big data analytics capabilities and supply chain performance: testing a moderated mediation model using partial least squares approach

Abstract: PurposeIn this study, the authors investigate the effect of big data analytics capability (BDAC) on supply chain performance (SCP) to assess the mediating effect of supply chain innovation (SCI) and the moderating effect of a data-driven culture (DDC).Design/methodology/approachThe authors collected the primary data through an online questionnaire survey from the manufacturing sector operating in Jordan. The authors used 420 samples for the final data analysis, which the authors performed via partial least squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 121 publications
2
24
0
Order By: Relevance
“…The recognition of the importance of emerging technologies in supporting performance in the supply chain is shown in the literature (Al-Khatib and Ramayah, 2023;Rajab et al, 2020;Ventura et al, 2023). Current recent studies have emphasized the importance of emerging technologies in improving efficiency, providing technological contributions and advanced analytical capabilities that transform the traditional supply chain form into a digital and smart form (Lohmer et al, 2022), providing several benefits at the level of the supply chain and the firms' organizational level.…”
Section: The Indirect Effect Of Scvmentioning
confidence: 99%
See 2 more Smart Citations
“…The recognition of the importance of emerging technologies in supporting performance in the supply chain is shown in the literature (Al-Khatib and Ramayah, 2023;Rajab et al, 2020;Ventura et al, 2023). Current recent studies have emphasized the importance of emerging technologies in improving efficiency, providing technological contributions and advanced analytical capabilities that transform the traditional supply chain form into a digital and smart form (Lohmer et al, 2022), providing several benefits at the level of the supply chain and the firms' organizational level.…”
Section: The Indirect Effect Of Scvmentioning
confidence: 99%
“…Firms operating in developing contexts, in particular the context of Middle Eastern countries, seek to adopt Industry 4.0 technologies in their manufacturing activities. A wide range of studies (Al-Khatib, 2022a, 2023a; Al-Khatib and Ramayah, 2023; Yavuz et al ., 2023) investigated the causal relationships between the adoption and use of Industry 4.0 technologies and the enhancement of supply chain performance and operational and organizational performance. Although these studies have investigated these relationships, there is a scarcity of empirical studies with theoretical and practical contributions that explore the relationships between Industry 4.0 technologies and sustainable performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The digital transformation age has witnessed considerable advances in data management and intelligent technologies that changed almost all business aspects such as financial, accounting, commerce, marketing, command and control. The enormous volumes of business data led firms to depend more on smart systems to assist in the analysis of big data and make the right decisions that support the firm's competitiveness (AL-Khatib and Ramayah, 2023; Khaw and Teoh, 2023). The fundamental objective of the cutting-edge technologies embedded in artificial business intelligence is to enhance new ways of collecting and analysing data that help companies improve their decision-making ethos by using data analytics (Nisar et al , 2020; Al-Khatib, 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge and literature studies, most scholars did not examine such a connection, which allowed me to investigate the linking of GT and employee knowledge efficiency in terms of the supply chain. In this association, the study of Al-Khatib and Ramayah (2023) analyzed supply performance based on data-driven culture. The study outcome indicated a positive connection between supply chain and innovation performance.…”
Section: Introductionmentioning
confidence: 99%